Research Progress in Separation of 99Mo - Jingyan ZHAO; Weidian WANG; Jixin LIANG; Yuxuan WU; Yijia SHEN (Journal of Isotopes)
As the parent nuclide of 99mTc，99Mo plays an important role for diagnosis in modern nuclear medicine.Fission products from uranium targets irradiated in nuclear reactors，besides 99Mo，a large amount of other radionuclides are produced during this process. Therefore，the highly efficient separation and purification for 99Mo from complex fission products has always been a major challenge. This article summarizes in two directions: new methods for the separation and purification of 99Mo in recent years，and optimization of existing processes. Emerging separation technologies，such as ionic liquid，cloud point extraction，gas phase separation and photo-controlled reaction，due to their high efficiency，environmental protection and easy operation，have shown great potential for application . This article also concludes the optimization method，automatic production，which not only improves the efficiency of separation and purification，but also enhances the safety of operators in the production process. With the continuous innovation of technology，it is expected that the more efficient，environmentally friendly and economical new processes will emerge to promote the sustainable development and upgrading of 99Mo industry in the future.